2008
DOI: 10.1104/pp.108.120196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence That Cellulose Synthase Activity Influences Microtubule Cortical Array Organization    

Abstract: To identify factors that influence cytoskeletal organization we screened for Arabidopsis (Arabidopsis thaliana) mutants that show hypersensitivity to the microtubule destabilizing drug oryzalin. We cloned the genes corresponding to two of the 131 mutant lines obtained. The genes encoded mutant alleles of PROCUSTE1 and KORRIGAN, which both encode proteins that have previously been implicated in cellulose synthesis. Analysis of microtubules in the mutants revealed that both mutants have altered orientation of ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(155 citation statements)
references
References 60 publications
10
143
2
Order By: Relevance
“…Indeed, ctl1-1 exhibited severe epidermal root cell swelling when grown in the presence of low levels of oryzalin (170 nM), while no apparent cell disturbance was observed in wild-type roots grown under the same conditions ( Figures 2C and 2D). Interestingly, similar microtubule defects and increased sensitivity to oryzalin have been reported for other cellulose-deficient mutants, such as kor1 (Paredez et al, 2008). It is plausible that the mainly longitudinal (E) Histogram of particle velocities.…”
Section: Mutations In Ctl1 Reduce the Velocity Of Primary Wall Cscsmentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, ctl1-1 exhibited severe epidermal root cell swelling when grown in the presence of low levels of oryzalin (170 nM), while no apparent cell disturbance was observed in wild-type roots grown under the same conditions ( Figures 2C and 2D). Interestingly, similar microtubule defects and increased sensitivity to oryzalin have been reported for other cellulose-deficient mutants, such as kor1 (Paredez et al, 2008). It is plausible that the mainly longitudinal (E) Histogram of particle velocities.…”
Section: Mutations In Ctl1 Reduce the Velocity Of Primary Wall Cscsmentioning
confidence: 77%
“…The CESA complexes (CSCs) are presumed to be assembled in Golgi bodies and transported to the plasma membrane where they are guided by cortical microtubules during cellulose synthesis (Haigler and Brown, 1986;Paredez et al, 2006). Once they are inserted in the plasma membrane, the CSCs move at constant rates, which may be reduced in mutants impaired in cellulose synthesis (Paredez et al, 2006(Paredez et al, , 2008. A population of small post-Golgi CESA compartments, called microtubule-associated cellulose synthase compartments (MASCs; Crowell et al, 2009)/small CESA compartments (SmaCCs; Gutierrez et al, 2009), may regulate the insertion and internalization of CESAs at the plasma membrane (Crowell et al, 2009;Gutierrez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…5 Hence, defects in cellulose synthesis have been reported to be related with alterations of microtubule orientation. [6][7][8][9] We recently showed that in Arabidopsis thaliana cellulose-deficient thanatos and pom2-4 mutants, of AtCesA3 and AtCSI1 respectively, suppression of cell expansion results in cortical microtubule reorientation in the fast elongation zone. 10 As both genes are involved in cellulose synthesis in primary cell walls, we examined the orientation of microtubules in 2 additional primary wall-related mutants, radially swollen1 (rsw1) 11,12 and procuste1 (prc1) 13 of AtCesA1 and AtCesA6, respectively.…”
Section: Cortical Microtubule Patterning Is Aberrant In the Fast Elonmentioning
confidence: 99%
“…Treatment with inhibitors of cellulose synthesis, including isoxaben or 2,6-dichlorobenzonitrile, led to a wider range of microtubule orientations in root tip cells (Himmelspach et al, 2003;Peng et al, 2013) and a reorientation of cortical microtubule arrays from a transverse to a longitudinal coalignment in cells at the root elongation zone (Paredez et al, 2008;Panteris et al, 2013). Disruption of normal microtubule organization also was observed in cases where mutations affected cellulose biosynthesis genes, including CESA1, CESA3, CESA6, CSI1, and KORRIGAN (Paredez et al, 2008;Panteris et al, 2013Panteris et al, , 2014. The notion of cell wall feedback is further supported by chemical and genetic perturbation of other cell wall components, including xyloglucans and arabinogalactans, that led to disorganization and reduced stability of cortical microtubules (Nguema-Ona et al, 2007;Driouich and Baskin, 2008;Xiao et al, 2016).…”
Section: Microtubule Interactions With the Cellulose Synthase Complexmentioning
confidence: 99%